2017
DOI: 10.1002/lno.10668
|View full text |Cite
|
Sign up to set email alerts
|

Photodissolution of copper from resuspended coastal marine sediments

Abstract: Total dissolved Cu (TDCu) was photoproduced from suspensions of estuarine and coastal marine sediments from varied biogeochemical settings after exposure to the equivalent of 1 day of sunlight. Net photorelease (defined as the difference between mean light and dark concentrations) of TDCu occurred in 10 of 13 experiments and ranged from 1.1 nM to 11.8 nM (0.88–46.1 nmol Cu g−1 dry sediment). Photorelease was observed over environmentally relevant total suspended sediment concentrations ranging from 38 mg L−1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Reconciling these previous estimates with our diagnosed rate of dissolved Cu input requires 0.77–1.81 Gmol Cu yr −1 of “new” dissolved Cu from shelf/slope sediments in oxygen‐replete margins or additional river input not included in prior estimates, as suggested by Richon and Tagliabue (2019). Photo‐dissolution of Cu from resuspended coastal sediments may contribute to this input as well (Skrabal et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reconciling these previous estimates with our diagnosed rate of dissolved Cu input requires 0.77–1.81 Gmol Cu yr −1 of “new” dissolved Cu from shelf/slope sediments in oxygen‐replete margins or additional river input not included in prior estimates, as suggested by Richon and Tagliabue (2019). Photo‐dissolution of Cu from resuspended coastal sediments may contribute to this input as well (Skrabal et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…A candidate source mechanism is photochemical reactions in the surface ocean, which previous studies have shown can destroy or cleave Cu-ligand complexes and increase the concentration of free Cu ions (Laglera & ven den Berg, 2006;Moffett & Zika, 1987;Shank et al, 2006;Tonietto et al, 2011). If Cu is photochemically solubilized from colloids or particles larger than 0.2-0.45 μm, this photodegradation could represent a source of dissolved Cu (smaller than 0.2-0.45 μm), as demonstrated by the photo-dissolution of organic-associated Cu from resuspended coastal sediments (Skrabal et al, 2018). (Paytan et al, 2009).…”
Section: 1029/2020gb006741mentioning
confidence: 99%
See 1 more Smart Citation
“…, it implies that there must be a significant pool of photoreducible iron(III) in the particulate phase. Previous studies have found a correlation between labile particulate minerals and dissolved metal concentrations following irradiation (Skrabal et al ), which suggests that in Big Fisherman's Cove, a significant amount of iron minerals may be relatively fresh oxyhydroxides. The increase in total dissolved iron concentrations throughout the day indicates that photoreduction and abiological processes are the dominant controls on iron cycling, as opposed to biological uptake and remineralization.…”
Section: Discussionmentioning
confidence: 91%